Model Pengelolaan Sumberdaya Manusia Pengelolaan Objek Wisata Religi Berbasis Kearifan Lokal - khuzaini, khuzaini; Setiadi, Budi; Irpan, Irpan (Jurnal Manajerial, 2024)
Background – The development of the tourism sector based on local wisdom, in supporting the sustainable tourism sector in Selayan Kalimantan, especially historical and religious tourism, namely mosques and tombs, is very much needed. Community-based tourism applications can be carried out in three stages, namely the planning stage, implementation stage and evaluation stage. Aim – The aim of this research is to analyze the concept and implementation of a combination of aspects of sharia-based human capital policy and local wisdom. Design/ Methodology/ Approach – This research is descriptive qualitative. Data collection in this article used in-depth interviews with 2 parties from managers and HRD. Apart from interviews, data was obtained through direct observation during employee selection and documentation. Findings – The research results showed that The development of religious tourism in South Kalimantan as sustainable tourism is very worthy of development, commitment to sustainable development, community involvement in decision making and management of religious tourism facilities and infrastructure that have previously existed, such as tombs, mosques and historical buildings. Efforts to optimize the development of sustainable religious tourism are developing the concept of cultural cities, increasing regional security, improving infrastructure and drainage in several places, providing new religious tourism attractions and more attractive additional attractions. Conclusion - The development of religious tourism in Banjar Regency has problems, namely (1) tourism facilities and infrastructure, (2) local resource development, and (3) marketing development. Research implication- It is hoped that there will be the obstacles that exist in religious tourism objects are related to facilities and infrastructure, weak local resources to support tourist attractions, and weak tourism marketing. To overcome obstacles, the strategies that can be implemented are related to the development of tourism facilities and infrastructure, development of local resources, and development of marketing. Limitations – Banjar Regency has quite large potential for developing religious tourism. There are 27 religious tourist attractions in Banjar Regency, but in reality most of the existing religious tourism has not been managed optimally..